생체적출안구에서 외안근의 해부학적 계측과 황반 및 시신경과의 관계 - 김정림; Jung Lim Kim; 이슬기; Sul Gee Lee; 양재욱; Jae Wook Yang (Daihan angwa haghoi jabji, 2008)
목적: 생체적출안구에서 외안근을 계측하고 사근, 황반, 시신경 간의 상호위치관계를 측정하여 기존의 사체안 대상 연구결과와 비교해 보고자 한다. 대상과 방법: 안구적출술을 받은 24안을 대상으로 각막윤부에서 외안근 부착부까지의 거리, 근폭 및 근간거리를 측정하여 기존 사체안 연구와 비교하였고, 안구를 절개한 후 황반에서 26게이지 바늘을 공막쪽으로 수직으로 관통시켜 안구 외측에서 황반, 시신경, 사근의 위치관계를 계측하였다. 결과: 윤부에서 상직근, 하직근까지의 거리가 Apt에 의한 기존 연구의 사체안과 유의한 차이가 있었다. 근폭은 모든 외안근에서 유의하게 좁게 측정되었다. 근간거리는 외직근과 상직근 사이, 상직근과 내직근 사이가 유의하게 좁았다. 시신경에서 황반까지의 거리는 3.99±0.62 mm, 상사근까지는 7.89±0.88 mm, 하사근까지는 5.95±0.83 mm였고 황반과 하사근 사이는 1.35±0.42 mm였다. 결론: 생체적출안구에서 외안근의 계측치는 기존의 사체안과 차이가 있었으며, 사체안의 보존 및 고정시의 근부피 변화, 인종간의 차이, 측정방법의 차이에 의한 것으로 추측된다. <한안지 49(7):1159-1164, 2008> Purpose: To make an anatomical evaluation of extraocular muscles, macular and optic nerve in enucleated eyes of live subjects and to compare the results with a previous autopsy study. Methods: Twenty-four surgically enucleated eyes were studied. The distance from the limbus to the muscle insertion site, muscle width, and the distance between muscle insertion sites were measured and compared with an Apt study. After an incision through the eyeball, a 26-gauge needle was passed perpendicularly through the macula to the sclera. We measured the distances between the oblique muscles and the macula and optic nerves from an external site of the eyeball. Results: The distance from the limbus to the muscle insertion site showed a significant difference in the superior and inferior rectus muscle. All measurements of muscle widths were significantly narrower than those of autopsy studies. The distances between the muscles were significantly closer between the lateral and superior muscles and between the superior and medial rectus muscles. From the optic nerve to the muscle was 3.99±0.62 mm, to the superior oblique muscle was 7.89±0.88 mm, to the inferior oblique muscle was 5.95±0.83 mm, and the macula to the inferior oblique muscle was 1.35±0.42 mm. Conclusions: Since most of the measurements were different from those of autopsy studies, we should consider the effects of preservation and fixation solution on autopsy eyes, race, and the differences among measurement instruments. J Korean Ophthalmol Soc 49(7):1159-1164, 2008